(untitled) (Bangladesh Journal of Agricultural Research, 2015)
An experiment was conducted during 2010 and 2011 to find out the suitable crop combination for increasing total productivity, return and maximize land utilization through intercropping system. Six treatments viz. Brinjal 100% + Red amaranth 100%, Brinjal 100% + Leaf amaranth 100%, Brinjal 100% + Jute as patshak 100%, Brinjal 100% + Mungbean 60%, Brinjal 100% + Blackgram 60% and sole of base crops (brinjal) were used in the study. Results showed that different intercropping combination did not influenced yield and yield contributing characters of brinjal. The yield of brinjal comparatively lower in intercropping but total productivity increased due to additional yield of leafy vegetables and legumes. The increases in total productivity in terms of brinjal equivalent yield (BEY) was 8.80 to 26.67 t/ha in intercrop combination compared to base crop. All the intercropping combinations were higher in terms of brinjal equivalent yield, gross return and benefit cost ratio (BCR) over sole crops. Among the intercropping combinations, Brinjal 100% (100 cm × 75 cm) + Mungbean 60% (three rows mungbean in between brinjal rows maintained 30 cm apart rows with continuous seeding) was the most feasible and profitable intercropping system in respect of brinjal equivalent yield (20.85 t/ha), gross return (Tk.312750/ha), gross margin (Tk.212693/ha) and benefit cost ratio (3.13). DOI: http://dx.doi.org/10.3329/bjar.v39i4.22548 Bangladesh J. Agril. Res. 39(4): 685-692, December 2014